Perceived Competence and Transition Experience of New Graduate Filipino Nurses - Nicolette Anne Ubas-Sumagasyay; Ryan Michael Oducado (Jurnal Keperawatan Indonesia, 2020)
Recruitment and hiring of new graduate nurses is seen as a potential strategy to mitigate the problem of nurse shortage. However, previous studies disclosed that new graduate nurses are inadequately prepared to enter practice and experience transition difficulties. This study aimed to determine the perceived competence and transition experience of new graduate Filipino nurses. Seventy-nine conveniently chosen new graduate nurses were surveyed in this descriptive cross-sectional research. Self-administered instruments were used to gather data. Descriptive statistics, Mann–Whitney U test, and Kruskal–Wallis test were the statistical tools employed. Results indicated that new graduate nurses had a high level of self-reported fundamental nursing skills (M= 7.99) and core competence (M= 8.16), although areas needing improvement were identified. There were no significant differences in the perceived competence based on the length of experience, year graduated, area of assignment, sex, type of school graduated, CPD participation, and hospital bed capacity (p> .05). The major difficulty experienced by new graduates during their transition was related to changes in role expectations (72.2%). Majority expressed the need for increased support during their transition (83.5%). The most satisfying aspects of their working environment were ongoing learning (81%) and peer support (74.7%), while the least satisfying was the negative nursing work environment (55.7%). New graduate nurses are equipped with the necessary nursing skills and core competencies. However, there are still gaps and areas needing improvement that should be addressed and supported to assist them in their transition to the world of professional nursing practice. Follow up, feedback, mentoring, and preceptorship are beneficial to enhance the competencies of new graduate nurses and facilitate their successful transition into the nursing workforce.
Keywords: 330; competency assessment; competence; new graduate nurses; novice nurses; nursing skills; transition experience